1993
DOI: 10.1182/blood.v81.1.158.158
|View full text |Cite
|
Sign up to set email alerts
|

The ABL-BCR fusion gene is expressed in chronic myeloid leukemia

Abstract: Although the BCR-ABL hybrid gene on chromosome 22q-plays a pivotal role in the pathogenesis of chronic myeloid leukemia (CML), little is known of the reciprocal chimeric gene, ABL-BCR, formed on chromosome 9q+. By reverse transcription/polymerase chain reaction amplification (RT/PCR) we have detected ABL-BCR mRNA in cells from 31 of 44 BCR-ABL positive CML patients and 3 of 5 CML cell lines. Of the 34 positive samples, 31 had classical t(9;22) (q34;q11) translocations; in 3 samples there was no Philadelphia (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(34 citation statements)
references
References 2 publications
1
32
0
1
Order By: Relevance
“…These data confirm that the fusion region of bcr3/abl2 contains immunogenic T‐cell epitopes, whereas immunogenic peptides from the bcr2/abl2 fusion region have not yet been clearly identified (Bocchia et al , 1995 and 1996). T cells recognizing abl/bcr were reported by Wagner et al (2003), nevertheless, abl/bcr expression at the protein level remains controversial (Melo et al , 1993). T‐cell responses against CML‐associated antigens did not show a clear‐cut TH1/TH2 cytokine pattern, which became particularly apparent in Patient 4 (Table V).…”
Section: Discussionmentioning
confidence: 99%
“…These data confirm that the fusion region of bcr3/abl2 contains immunogenic T‐cell epitopes, whereas immunogenic peptides from the bcr2/abl2 fusion region have not yet been clearly identified (Bocchia et al , 1995 and 1996). T cells recognizing abl/bcr were reported by Wagner et al (2003), nevertheless, abl/bcr expression at the protein level remains controversial (Melo et al , 1993). T‐cell responses against CML‐associated antigens did not show a clear‐cut TH1/TH2 cytokine pattern, which became particularly apparent in Patient 4 (Table V).…”
Section: Discussionmentioning
confidence: 99%
“…While the bcr-abl gene is expressed in the majority of the chronic myelogenous leukemia patients (CML), the abl-bcr expression can be detected by RT-PCR in only about 59-70%. 1,2 In most of the analyzed cases with rearrangements in the major region of the BCR gene, the junction type in bcr-abl was exactly reciprocal to the junction in bcr-abl, eg a bcr-abl hybrid gene of the type b2-abl correlates with an abl-bcr hybrid gene abl-b3. However, in some cases neither transcripts correlated one with the other.…”
Section: To the Editormentioning
confidence: 98%
“…These cases included b2-abl patients that expressed only abl-b4 transcripts, thus missing the b3 exon, and b3-abl patients that showed an unexpected abl-b3 hybrid either alone or together with the expected abl-b4 transcript. 1 In the first case, the deletion of the b3 exon could be explained if the deletion took place in the b3 exon itself, or if this exon was included in deletions at the breakpoint site. However, in the second case, only a duplication of the b3 exon could explain this discrepancy.…”
Section: To the Editormentioning
confidence: 99%
“…Using manual checks and selection, we identified that the majority of fusion events occurred between adjacent genes on the same chromosome, which were usually regarded as read-through (21), while only two candidates, including RNF213-SLC26A11 and BCR-ABL1, were the most reliable gene fusion pairs. BCR-ABL is a well-documented gene fusion in CML and is used as a standard method for CML diagnosis (22). The RNF213-SLC26A11 fusion has not been previously identified in CML.…”
Section: Improvement Of Filtering Gene Fusionmentioning
confidence: 99%